Visual Communication Design for Mobile Learning Apps: User Interface Usability and Learning Engagement - Jingmiao, Yang (Comunicar, 2024)
This study explored the visual communication design for the mobile learning applications through user interface usability and learning engagement. This experiment also observed the mediating impact of cognitive load in the relationship between user interface usability and learning engagement. The method adopted for the study was quantitative method and the data was collected by adopting a questionnaire survey strategy. The data was collected from the higher education institutions in China located at different regions and the target population of the study were the current enrolled students at these institutions. The study tested the research hypotheses through structural equation modelling. CFA was used to evaluate the fitness of the measurement model. The findings of the study indicated that user interface, and student engagement were effective indicators of visual communication design. The study would be a great contribution as it dealt with emerging topic of visual communication design in the educational sector of China, advocating the use of mobile learning applications. The study would also offer significant insights to managers and policy makers. Future researchers could maneuver qualitative research design to analyze the perspectives, viewpoints and subjective opinions in the subject.